Roles, challenges, and resiliency during the COVID-19 pandemic: a case of women political leaders in the Philippines - Patalinghug, Mark Erana; Majorenos, Ann Mariel P.; Tigley, Rezin I. (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
Since the onset of the COVID-19 pandemic, there has been substantial scholarly interest in the roles of women in leadership positions. This multiple-case study explores the experiences of female political leaders during the pandemic, focusing on their roles, challenges, and resilience. The study encompasses ten women political leaders actively involved in pandemic-related activities in Dumingag, Zamboanga del Sur, Philippines. The findings indicate that these women embodied exceptional compassion and courage in their efforts to curb the virus's spread within their communities. The research underscores that the attributes traditionally associated with femininity, such as empathy and nurturing, were beneficial during the pandemic. Rather than posing a challenge, femininity complemented their leadership roles, with the main obstacles being the risk of contracting COVID-19 and public skepticism regarding the pandemic's seriousness. The study highlights that these female leaders adeptly managed the pandemic's challenges through effective cooperation and collaboration with stakeholders, underpinned by a commitment to altruism. This research contributes to the field by demonstrating that the qualities associated with female leadership can enhance crisis management. It informs the international debate on gender and leadership, suggesting that women's distinctive attributes may be particularly advantageous in navigating global health emergencies. By emphasizing these contributions, the study advocates for a broader recognition of the value of female leadership in crisis situations and encourages further examination of gender dynamics in leadership roles globally.